A review of nanocarrier-mediated drug delivery systems for posterior segment eye disease: challenges analysis and recent advances. (9th August 2021) - Wang, Rui; Gao, Yuan; Liu, Anchang; Zhai, Guangxi
Abstract: Posterior segment eye disease is a leading cause of irreversible vision impairment and blindness. As the unique organ for vision, eyes are protected by various protective barriers. The existence of physiological barriers and elimination mechanisms makes it challenging to treat the posterior segment eye diseases. To achieve efficient drug delivery to the posterior segment of eyes, different drug delivery systems have been proposed. Due to their abilities to enhance ocular tissue permeability, make controlled drug release and target retina, nanocarriers, such as lipid nanoparticles, liposomes and polymeric nanomicelles, have been widely studied for posterior segment drug delivery. However, clinical applications of nanocarrier mediated drug delivery systems as non-invasive ocular drops is still not ready. The delivery of nanocarrier-mediated drug for posterior segment disease still faces the choice of being more effective or more invasive for long-term treatment. Therefore, it is necessary to have a clear understanding of the barriers and the routes of ocular drug delivery while developing the delivery systems. In this review, types of ocular barriers and drug administration routes are categorised in a more intuitive way. Recent advances in nanocarrier mediated drug delivery systems with focus on posterior segment are reviewed with illustrative examples.